Safety and efficacy of vaginal misoprostol versus transcervical foley catheter and intravenous oxytocin for induction of labour - Orji, Ernest O (Nepal Journal of Obstetrics and Gynaecology, 2014)
Introduction: A variety of drugs were used for induction of labour, but only oxytocin and prostaglandins have survived critical test of effectivity with a minimum of side effects for mother and child. The objective of this study is to compare efficacy and safety of vaginal misoprostol with transcervical Foley’s catheter and intravenous oxytocin for induction of labour. Methods: Eighty women at term gestation with the Bishops score < 4 with various indications for labour induction were randomly allocated to receive 25 microgram misoprostol vaginally 4 hourly (maximum 6 doses) or transcervical Foley’s catheter with intravenous oxytocin (2mU/minute to a maximum of 32mU/ minute). There were 40 women in each group. Result: In the misoprotol group induction delivery interval was significantly less (5.50 versus 15.0 hours) and successful induction significantly higher (95% versus 75%) as compared to catheter/oxytocin group. There were more cases of hyperstimulation with misoprostol; however neonatal outcome was similar in both groups. There were more vaginal delivery and less caesarean section in misoprostol compared to Foley’s catheter/oxytocin group. Conclusion: Vaginal misoprostol is highly effective, safe to administer as an agent for induction of labour DOI: http://dx.doi.org/10.3126/njog.v3i2.10825 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 12-15